2014
DOI: 10.3109/09638288.2014.963706
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of studies reporting multivariable models to predict functional outcomes after post-stroke inpatient rehabilitation

Abstract: Only a selected group of variables have repeatedly proven to be significant predictors of functional ability after post-stroke inpatient rehabilitation. [Box: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
136
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 33 publications
8
136
1
8
Order By: Relevance
“…First is that it is not known whether the independent variables used in the present study was appropriate or not. In their review of multiple regression analysis performed on acute phase stroke patients, Meyer et al [15] found that in 27 studies, 63 out of 126 factors used as independent variables were significant. However, the number of significant independent variables actually included in a single predictive formula was an average of no more than 4.1 (standard deviation of 2.5) [15].…”
Section: Discussionmentioning
confidence: 99%
“…First is that it is not known whether the independent variables used in the present study was appropriate or not. In their review of multiple regression analysis performed on acute phase stroke patients, Meyer et al [15] found that in 27 studies, 63 out of 126 factors used as independent variables were significant. However, the number of significant independent variables actually included in a single predictive formula was an average of no more than 4.1 (standard deviation of 2.5) [15].…”
Section: Discussionmentioning
confidence: 99%
“…In the review of Meyer et al [4], R 2 was on average 0.65 (minimum 0.35 to the maximum 0.82) when the objective variable was FIM at discharge, 0.22 (0.08 to 0.4) when the objective variable was FIM gain (FIM at discharge minus FIM at admission), and 0.08 (0.03 to 0.14) when the objective variable was FIM efficiency (FIM gain divided by the number of days in hospital). For accurate prediction, it is necessary that R 2 is 0.5 or more (desirably 0.7 or more).…”
Section: What Should We Use As the Objective Variable?mentioning
confidence: 99%
“…Factors that were used in more than five prediction formulas and were significant in more than half of them were FIM at admission (significant in 46 formulas of 51 formulas, 46/51), age (30/45), previous stroke (5/10), Barthel Index at admission (6/6), neglect (4/6), dysphasia (4/6), impulsivity (4/6), and National Institute of Health Stroke Scale (5/5) [4]. However, the number of significant explanatory variables incorporated into one prediction formula was only 4.1 on average [4]. Furthermore, the Japanese Guidelines for the Management of Stroke 2015 [5] says that "even if the variables used for prediction are simply increased, the prediction accuracy does not necessarily rise [6,7], and the advantages of using the simplest prediction method are also shown [8]".…”
Section: Using Appropriate Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations